Effects of a Self-Efficacy Promotion Program Using Infographics on Perceived Self-Efficacy Perception and Language Development Promotion Behaviors for Preschool Children Among Early Childhood Teachers - Promkanya, Anucha; Parasri, Amornrat (Journal of health and health management, 2025)
This quasi-experimental research study utilized pre-test and post-test designs to investigate the effects of a perceived self-efficacy enhancement program that employed infographic media. The sample consisted of 40 early childhood teachers from child development centers in the Mueang District of Chaiyaphum Province, divided into an experimental group of 20 and a control group of 20. The instruments used in the study included a general information questionnaire, a perceived self-efficacy questionnaire, and a language development promotion behavior questionnaire, with content validity ranging from .64 to 1.00 and reliability values of .72 and .80, respectively. Data were analyzed using means, standard deviations, and t-test statistics. The findings indicated that, following the experiment, the experimental group demonstrated higher mean scores for perceived self-efficacy ( = 113.30, SD = 2.33) and language development promotion behavior ( = 105.35, SD = 2.30) in comparison to the control group (perceived self-efficacy: = 101.30, SD = 3.21; language development promotion behavior: = 89.80, SD = 1.70), with a statistically significant difference at p < .05. Additionally, the experimental group’s mean scores for both perceived self-efficacy and language development promotion behavior were significantly higher after the experiment than before (p = .001). This research can serve as a guideline for developing infographic media designed to enhance the perceived self-efficacy of early childhood teachers. Additionally, it can be utilized as a model for creating teacher development resources in other areas that align with the specific contexts and needs of educational institutions.